Reproduction and Mortality of Finnish Semi-Domesticated Reindeer in Relation to Density and Management Strategies - Helle, T.; Kojola, I. (ARCTIC, 1993)
We assessed the effects of management strategies during 1960-73 relative to strategies used during 1974-87 on the reproduction and mortality of 56 semi-domesticated herds of Finnish reindeer (Rangifer tarandus tarandus). During 1960-73, reindeer fed exclusively on natural forage growing on their range, and reindeer were harvested mostly as adults. These strategies were modified starting in 1974 to include supplemental feeding in the southern part of the Finnish reindeer range and calf harvesting throughout the range. We found significantly higher calf/female ratios, lower mortality, and less variation in both calf/female ratios and mortality during 1974-87 than during 1960-73. These changes occurred in spite of increased animal density. Coefficients of variation in calf/female ratio and mortality were negatively correlated with the prevalence of mature spruce forests, which are rich in arboreal lichens. Mean calf/female ratio and mortality rate depended on reindeer density only in the southern region during 1960-73. During 1974-87 these did not depend on density in any region. Within herds, calf/female ratio did not depend on density in most cases (98%), while in the later period the relationship between calf production and density was positive in some cases (25%). Mortality depended more often on density during the earlier (46% of herds) than the later (23% of herds) period. Calf harvesting influenced mortality more than supplemental feeding and virtually freed reindeer from density-dependent limitations. Supplemental feeding was used to compensate for deterioration of range resulting from overgrazing and logging of mature forests rich in arboreal lichens.Key words: reproduction, mortality, density dependence, reindeer, Rangifer tarandus, management, Finland On a évalué les retombées des stratégies d'aménagement utilisées entre 1960 et 1973 par rapport à celles utilisées de 1974 à 1987 sur la reproduction et la mortalité de 56 troupeaux semi-domestiques de caribous finlandais (Rangifer tarandus tarandus). Au ...